The Relationship Between Knowledge of Dental Caries and the Incidence of Dental Caries in Pregnant Women at Polindes Jungkarang, Sampang, Madura - Kamiliyatun Nisaa'; Bambang Hadi Sugito; Sunomo Hadi (International Journal of Advanced Health Science and Technology, 2024)
Problem: Based on primary data collected from pregnant women at Polindes Jungkarang, Sampang Regency, the average DMF-T score was 5.37, indicating that dental caries in pregnant women is still in the high category. This has not yet reached the target set in the National Action Plan (RAN), where the DMF-T value should be 4.1 for all ages. Research Objective: To determine the relationship between knowledge about caries and the high incidence of dental caries in pregnant women at Polindes Jungkarang, Sampang Regency. Research Method: This research is an analytical study using a cross-sectional method, with a sample of pregnant women visiting Polindes Jungkarang, Sampang Regency, from January to March 2024. The data collection instruments used were a questionnaire to measure knowledge about dental caries and a DMF-T examination sheet to identify caries. The analysis technique used was Spearman's rho test. Results: There is a relationship between knowledge about caries and the high incidence of dental caries in pregnant women at Polindes Jungkarang